Asking questions that are “close to the bone”: integrating thematic analysis and natural language processing to explore the experiences of people with traumatic brain injuries engaging with patient-reported outcome measures - Di Basilio, Daniela; King, Lorraine; Lloyd, Sarah; Michael, Panayiotis; Shardlow, Matthew (Frontiers in Digital Health, 2024)
In the context of mental health in individuals with TBIs, PROMs have been repeatedly used in clinical and research practice to assess domains that are commonly negatively influenced by TBIs. These include, for example, global functioning, neuropsychological impairment, adjustment problems, and or mood disturbances (Wilde et al. 2010), with particular relevance given to the evaluation of anxiety and depression as common TBI comorbidities (Osborn et al. 2017;Hammond et al. 2021;Delmonico et al. 2022). A growing number of studies increasingly highlighted the importance of taking into account patients' perspectives when assessing these domains and when planning and evaluating treatment outcomes (Kaplan et al. 2021;Duncan and Murray 2012;Schrier et al. 2016).Focusing on the experiences and views of patients when administering and scoring PROMs can serve different purposes, including supporting patients' understanding of their symptoms, enhancing communication and treatment management and facilitating discharge planning (Deutscher et al. 2008;Duncan and Murray 2012). Despite the advantages of routine outcome measures, their implementation in the context of traumatic brain injuries is not without challenges. Issues such as variability in injury severity, cognitive impairments, and the need for specialised measures may present hurdles that may necessitate careful consideration and adaptation of PROMs (Wilson et al. 2022;Wilde et al. 2010). Among others, barriers to completing PROMs for TBI patients include cognitive demands associated with PROMs completion, memory issues that can alter the possibility of accurately recalling symptoms, potentially impaired self-awareness, and cognitive biases (